PID Control and Robust Control - Gaofeng, Zhou; Qi, Zhang (Modern Control Systems: Theory, Design and Applications, 2025)
This chapter focused on two themes: PID control and robust control. Firstly, the basic adjustment laws of PID (Proportional-Integral-Differential (Controller), PID) control were narrated and explored. Then relatively specific control laws deduced from the PID controller were provided for readers. On the basis of PID control, robust control was introduced to realize the application of robust control in application.